1996
DOI: 10.1557/jmr.1996.0310
|View full text |Cite
|
Sign up to set email alerts
|

Highly resistive sputtered ZnO films implanted with copper

Abstract: Polycrystalline (0001)-oriented thin films of ZnO (thickness 120 nm) were deposited by rf magnetron sputtering and post-deposition annealed at 500 °C in oxygen (1 atm). The films were subsequently implanted with copper at doses over the range 1016 to 1017 ions/cm2. X-ray diffraction (XRD) indicates the compressive intrinsic film stress is largely relieved by the preimplantation anneal, and does not change when implanted or when further annealed after implantation, suggesting that the dominant cause of intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The appearance of a Cu 2p satellite implies that the Cu 2+ exists and the satellite intensity and position are also dependent on the atomic environment of the Cu 2+ . The Cu 2+ has a higher binding energy shoulder and weak satellite at approximately 943 eV [16]. Also, the Cu 3d orbital of Cu 1+ are filled as 3d 10 4s 0 (Cu)-2p 6 (O).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of a Cu 2p satellite implies that the Cu 2+ exists and the satellite intensity and position are also dependent on the atomic environment of the Cu 2+ . The Cu 2+ has a higher binding energy shoulder and weak satellite at approximately 943 eV [16]. Also, the Cu 3d orbital of Cu 1+ are filled as 3d 10 4s 0 (Cu)-2p 6 (O).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the Cu 3d orbital of Cu 1+ are filled as 3d 10 4s 0 (Cu)-2p 6 (O). In contrast, the Cu 2+ has a 3d 9 4s 0 (Cu)-2p 6 (O) valence band configuration and may therefore trap electrons with the Cu 3d hole state [16]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements on sputtered zinc oxide thin films that have been annealed in oxygen (to remove oxygen vacancies) have been found to have an electrical resistivity of 5 x 10 10 Ω.cm 13 . In contrast, when the top electrode was sputtered onto the surface of the films for optical interferometric measurements, the electrical resistivity across the thickness of the film (from top electrode to bottom electrode) was very low (<5 x 10 4 Ω.cm).…”
Section: Optical Interferometric Measurements (Global Piezoelectric Ementioning
confidence: 99%
“…The electron trap level of Cu doped ZnO was studied by Furukawa et al [11]. Also the other research groups found that the resistivity of the ZnO films increased with an increase in Cu concentration [9][10][11]. The current-voltage (I-V) characteristics of ZnO may be either linear or non-linear depending on the electrode-film contact as well as inherent defects controlled electron transport properties.…”
Section: Introductionmentioning
confidence: 99%